Diri dan Pengetahuan Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Medan - Yossi Suryandani Sitorus; Amrin Mulia Utama Nasution; Tohap Parulian (Economics, Business and Management Science Journal, 2021)
The purpose of this study was to determine and analyze the effect of self-concept and knowledge on employee performance at the Medan Public Works Department. The research method used is associative research, where variables are measured with a Likert scale. Data collection methods by interview, questionnaire and observation. In this study the sample used was 80 respondents. Data management uses smartPLS3 with Structural Equation Modeling (SEM) analysis. The results showed that: (1) partially the self-concept variable influenced the performance of employees in the Medan Public Works Department by 5,825 (2) partially the knowledge variable affected the performance of the employees at the Medan Public Works Department by 7,738. R-Square value obtained is 0.642. To see the effect of independent variables on the dependent variable by calculating the coefficient of determination shows that 64.2% the remaining 35.8% is influenced by other factors not explained in this study.